Food delivery business: a new trend in 2020 / Siti Noor Syalwani Mustapa ... [et al.] - Mustapa, Siti Noor Syalwani; Anuar, Azyyati; Mohd Piah, Zainuddin (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
According to Milo (2018), the online food delivery business seems to be the fastest-growing food market sector. It is projected to grow to annual revenue of USD 956 million by 2020. Several factors prompted the change in preference of citizens from the traditional offline food delivery purchase to online food delivery service. The most common reason seems to be the need for quick and convenient meals during and after a busy workday. Time-saving is a major contributing factor that influences people's behavioral intention to purchase online (Khalil, 2014 & Orpilla, 2020). Shopping online is time-saving because shoppers do not need to leave the current place to purchase something physically. The various food delivery services that are readily available may help consumers think and plan meals, regardless of whether the consumers are preparing the meal themselves, going to the restaurant and dining in, or going to the restaurant and buying food to bring back the food to their home or office. Many prefer food delivery as this allows them to have fresh and healthy food at their offices or homes while they have the freedom to continue working. Yeo et al. (2017) found that consumers would prefer food to come to them without much effort and to be delivered as fast as possible